An exploratory study on CLU, CR1 and PICALM and Parkinson disease. - Jianjun Gao; Xuemei Huang; Yikyung Park; Albert Hollenbeck; Honglei Chen (PLoS ONE)
Background Recent GWAS and subsequent confirmation studies reported several single-nucleotide polymorphisms (SNPs) at the CLU, CR1 and PICALM loci in association with late-onset Alzheimer's disease (AD). Parkinson disease (PD) shares several clinical and pathologic characteristics with AD; we therefore explored whether these SNPs were also associated with PD risk. Methodology/principal findings 791 non-Hispanic Whites cases and 1,580 matched controls were included in the study. Odds ratios (OR) and 95% confidence intervals (CI) were obtained from logistic regression models. rs11136000 at the CLU locus was associated with PD risk under the recessive model (comparing TT versus CC+CT: OR = 0.71, 95% CI: 0.55-0.92, p = 0.008) after adjusting for year of birth, gender, smoking, and caffeine intake. Further adjustment for family history of PD and ApoE ε4 status did not change the result. In addition, we did not find evidence for effect modification by ApoE or known PD risk factors. The association, however, appeared to be stronger for PD with dementia (OR = 0.49, 95% CI: 0.27-0.91) than for PD without dementia (OR = 0.81, 95% CI: 0.61-1.06). The two other SNPs, rs6656401 from CR1, and rs3851179 from PICALM region were not associated with PD (p>0.05). Conclusion Our exploratory analysis suggests an association of CLU with PD. This exploratory finding and the role of dementia in explaining this finding needs further investigation.